STRUKTUR FORMAL DALAM GEGURITAN JAMBE NEGARA - Sukma Wirani, Ida Ayu (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2013)
The main objective of this study is to determine the formal structure in Geguritan Jambe Negara, and to contribute to the community in an effort to develop a literary treasures of Bali. This is a descriptive study with the method of observation and literature with the help of recording and translation techniques. Objects in this study is Geguritan Jambe Negara-owned Puri Gede Krambitan Tabanan. Disclosure of the contents of Geguritan Jambe Negara is the formal structure geguritan. In the formal structures of the Geguritan Jambe Negara language code that contains a wide variety of Bali Alus language, and Bali Kasar language Coarse language and style found in Geguritan Jambe Negara is such a style; hyperbole, litotes, oxymoron, eponym, antonomasia. The second result is a distortion in the literary code GJN occurred on the last syllable vocals, and deviations wilaiyin teacher. The deviation is a creative writer to retain the meaning or story in the geguritan.Keywords: formal structure, geguritan, and literary Bali